Transcriptional regulatory mechanism of early defense response of oil palm against Ganoderma boninense - Abdul Bahari, Mohammad Nazri; Mohd Sakeh, Nurshafika; Abdullah, Siti Nor Akmar; Ramli, Redzyque Ramza; Kadkhodaei, Saied (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Basal stem rot (BSR) caused by Ganoderma boninense, a white-rot fungus is one of the major threats in oil palm industry that accounted for huge economic losses. Furthermore, the defense mechanism of oil palm against G. boninense infection is poorly understood. Elucidation of the molecular changes in defense response in oil palm at early stages of the fungal colonization where symptoms have not yet appeared will promise further insights for prevention measures. Whole transcriptome RNA sequencing (RNA-Seq) was performed on G. boninense-infected oil palm seedlings at 3, 7, and 11 days post inoculation (d.p.i.). Analysis on differentially expressed genes (DEGs) revealed strengthening of the plant cell wall as well as degradation of fungal cell wall through chitinase activity. Flavonoids were suggested to be synthesized at later stage (7 and 11 d.p.i). Besides, 1-aminocyclopropane-1-carboxylate synthase (involves in ethylene biosynthesis) and MYC2 transcription factor genes were observed significantly induced at from 3 – 11 d.p.i. Both of the genes presumably work in concert at early interactions between oil palm and G. boninense. This study further clarifies the roles of defense response genes in oil palm at early stages of interaction with G. boninense.